Strong inhibition of xanthine oxidase and elastase of Baccharis trimera (Less.) DC stem extract and analysis of biologically active constituents - Song, Seung-Yub; Lee, Sung-Ho; Bae, Min-Suk; Park, Dae-Hun; Cho, Seung-Sik (Frontiers in Pharmacology, 2023)
In the present study, strong xanthine oxidase and elastase activities of Baccharis trimera (Less) DC stem (BT) were evaluated and active ingredients were identified to determine the possibility of using BT extract as an anti-hyperuricemia (gout) and cosmetic functional material. Hot water, 20, 40, 60, 80, and 100% ethanolic extracts of BT were prepared. The hot water extract had the highest extraction yield whereas the 100% ethanolic extract had the lowest yield. Antioxidant effects were investigated based on DPPH radical scavenging activity, reducing power, and total phenolic contents. The 80% ethanolic extract showed the highest antioxidant activity. However, the 100% ethanol BT extract showed strong xanthine oxidase and elastase inhibitory activities. Functional substances were thought to be caffeic acid and luteolin. Minor active substances such as o-coumaric acid, palmitic acid, naringenin, protocatechoic acid, and linoleic acid were identified. Through this study, we firstly reported evidence that BT stem extract could be used as functional materials with anti-hyperuricemia and skin disease improving effects. BT stem extract could be used as an anti-hyperuricemia (gout) natural drug or cosmetic material. For further study, practical studies such as optimizing BT extraction and functional experiments for hyperuricemia(gout) and skin wrinkle improvement are considered necessary.